(untitled) (Journal of Population and Development, 2022)
This study opportunities and challenges of bamboo based entrepreneurship was carried out in Badikhel area of Lalitpur district, Nepal. This paper is a descriptive study focused to assess the opportunities and challenges of bamboo based entrepreneurship. Both primary and secondary data were used. Questionnaire, key informants interview, focus group discussion were used to coined the required information. The quantitative data are presented in tabulator form and qualitative data are interpreted as a narrative form. The study showed traditional marketing strategy, lack of resources, traditional skills, and transportations, lack of opportunities, lack of financial knowledge and lack to access to financial institutions are major challenges while promoting the bamboo based enterprises. However, this study proved that these entrepreneur, identified good opportunities, practice on equal wage for same work, initiate their ventures and they have formulated plan. The study indicated that financial access, training facilities, government subsidy, etc. are opportunities in this regard. Pahari were socialized in farming, husbandry, bamboo winning, bamboo crafting and now some people are shifting others. There are some recommendations that could uplift the micro enterprises in Nepal. Without entrepreneurship rural area cannot be developed, thus, good policies and plan must formulate and implement as well with sufficient financial and technical support by local government and development stakeholders. The verbal consent was taken while collecting the data.